2011
DOI: 10.1037/a0024238
|View full text |Cite
|
Sign up to set email alerts
|

Hearing loss and cognition in the Baltimore Longitudinal Study of Aging.

Abstract: Objective To determine the relationship between hearing loss and cognitive function as assessed with a standardized neurocognitive battery. We hypothesized a priori that greater hearing loss is associated with lower cognitive test scores on tests of memory and executive function. Methods A cross-sectional cohort of 347 participants ≥ 55 years in the BLSA without mild cognitive impairment or dementia had audiometric and cognitive testing performed in 1990–1994. Hearing loss was defined by an average of hearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
537
4
12

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 608 publications
(585 citation statements)
references
References 76 publications
32
537
4
12
Order By: Relevance
“…This result not only confirms previous studies but also what was expected by the researchers, since it has been described in both national and international literature 5,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] . The age of the individuals caused an increase in auditory thresholds, which may lead to an even more harmed speech comprehension.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This result not only confirms previous studies but also what was expected by the researchers, since it has been described in both national and international literature 5,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] . The age of the individuals caused an increase in auditory thresholds, which may lead to an even more harmed speech comprehension.…”
Section: Discussionsupporting
confidence: 81%
“…Previous researches revealed similar findings, 7,27-31 therefore proving the association between hearing and cognitive decrease 32,33 .…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…[9,10] Such hearing loss is predominantly high frequency and sensorineural. Lin et al [11,12] reported that older adults with hearing loss are more likely to develop cognitive impairment and dementia than their contemporaries without hearing loss. Regular monitoring and early detection and treatment of presbycusis would maintain an existing quality of life.…”
Section: High-risk Groups Presbycusismentioning
confidence: 99%
“…This fact presents a clinical challenge to optimizing outcomes for the expanding population of CI users because cognitive functions decline with advancing age. That fact could further compromise speech recognition in this population of patients with hearing loss (Lin et al, 2011(Lin et al, , 2013.…”
mentioning
confidence: 99%